Some aspects of enisamium iodide nasal spray safety: pre-clinical study results - Zhulai, Tetiana; Zupanets, Igor; Shebeko, Sergii; Zimin, Stanislav; Yampolska, Kateryna (ScienceRise: Medical Science, 2020)
The aim. To substantiate the safety using of the new nasal spray with Enisamium Iodide via study results of acute local drug-induced irritant action of the test object single-dose to eyes and nasal cavity mucosa. Material and methods. Enisamium Iodide 10 mg/mL (nasal spray) was the test object. The reference drug was 0.9 % saline. Flemish Giant rabbits were used to induce the experiment (2 groups, 9 rabbits in each group). All study objects were administered in single-dose into the eye conjunctival sacs (0.01 mL) and nasal passages (0.1 mL) by instillation. The eye examination we performed in different time observation point (through 1, 24, 48 and 72 h after drug instillation). Nasal endoscopy was used for control of nasal cavity in all stages of study (15 minutes before, 1-hour and 24 hours after drug instillation) under general anesthesia. The scales of the assessment were used to the result objectivity. Results. The total score was 0 points in all groups at all-time points according to the relevant scale and the scale of the assessment of rabbit nasal cavity mucosa by nasal endoscopy results. This corresponds to the condition of a healthy eye and healthy nasal mucosa. Conclusions. Enisamium Iodide 10 mg/mL (nasal spray) in the single-dose instillation into the rabbit eye conjunctival sacs and rabbit nasal passages did not show local drug-induced irritant action on the eye conjunctiva and nasal cavity mucosa in the experimental animals. Nasal endoscopy could be used as an informative visual method in preclinical studies